Comprehensive corrective feedback in foreign language writing: The response of individual error categories - Bonilla López, Marisela (2021)
While the literature on the effect of comprehensive corrective feedback (CF) on overall accuracy is abundant, the body of work employing such a scope to explore error treatability is not, especially when it comes to blended (cf. Ferris, 2010) design studies. Consequently, this investigation extends the analyses from the data set of Bonilla et al. (2018) to report on individual linguistic features. Specifically, to address crucial amenabilityrelated questions in need of perusal, the present blended design study explores the effect of two types of comprehensive CF (with direct correction and metalinguistic codes) on the treatability of separate grammatical and non-grammatical structures. To this end, a group of EFL learners (N = 139) were required to do editing that involved error-correction, deferred (on a draft), and focused on language as well as to produce two independent essays (in an immediate and a delayed posttest). Main results from logistic regression (to test the effect in revised essays) and mixed-effect models (to test the effect on independent essays) render seven variables that can explain correctability differences: out of those, three have also explained overall accuracy gains (cf. Bonilla et al., 2018), one has not been identified thus far, and three consolidate themselves as relevant factors under other conditions as well. Theoretical and pedagogical implications are discussed.